Ekonomické a environmentální hodnocení energeticky úsporných opatření na rezidenčních budovách - Dosedělová, Pavla (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Bakalářská práce se zabývá energeticky úspornými opatřeními panelových domů, jejich vlivem na životní prostředí a ekonomickou efektivností. V teoretické části jsou jednotlivá opatření popsána a jsou definovány možné způsoby ekonomického a environmentálního hodnocení. Praktická část se zabývá dvěma již realizovanými případy zateplení panelových domů.

The Bachelor Work goes into energy conservation measures of prefabricated blocks of flats, it deals with their effect on the environment and economic efficiency. In the theoretical part particular measures are described and possible economic and environmental assessment methods are defined. The practical part is devoted to two already realized cases of the thermal insulated prefabricated blocks of flats.
Economic and Environmental Evaluation of Energy Saving Measures on Residential Buildings
Keywords: Energeticky úsporná opatření; zateplení; panelový dům; investice; úspora; čistá současná hodnota; doba návratnosti; emise; oxid uhličitý.; Energy conservation measures; thermal building insulation; prefabricated block of flats; investment; saving; net present value; period rates of return on investment; emissions; carbon dioxide.